problem one:

ax = bx +c

the answer is:

x = c/(a-b)

problem two:

ax - b = cx + d

the answer is:

x = (d+b)/(a-c)

I'm pretty lost here, and would appreciate any help.

Printable View

- Dec 26th 2012, 03:03 PMsweezybasic solving for x
problem one:

ax = bx +c

the answer is:

x = c/(a-b)

problem two:

ax - b = cx + d

the answer is:

x = (d+b)/(a-c)

I'm pretty lost here, and would appreciate any help. - Dec 26th 2012, 03:42 PMProve ItRe: basic solving for x

Can you follow a similar process to solve the second one? - Dec 26th 2012, 05:10 PMsweezyRe: basic solving for x
ax - b = cx + d

ax = cx + (d + b)

ax - cx = (d + b)

x (a - c) = (d + b)

x = (a - c)/(d + b)

Thank you, it's clear to me now even if it doesn't seem so without the tex tags. - Dec 27th 2012, 10:39 AMearbothRe: basic solving for x